2018
DOI: 10.2147/ppa.s179629
|View full text |Cite
|
Sign up to set email alerts
|

The impact of fatwas on patients’ acceptance of enamel matrix derivatives for periodontal regeneration in Saudi Arabia

Abstract: BackgroundSince the introduction of enamel matrix derivatives (EMD) (Emdogain®), it has not been allowed to be used in Saudi Arabia due to the religious restriction on porcine products. This study was conducted to determine the impact of the fatwas permitting the use of EMD and to assess the general perception of using bone-grafting materials in Jeddah, Saudi Arabia.Materials and methodsThis cross-sectional survey study included 213 patients seeking dental treatment at the Faculty of Dentistry Clinics of King … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 19 publications
(21 reference statements)
0
2
0
Order By: Relevance
“…Several studies involving participants who are Muslim found bone graft materials based on xenografts, especially from porcine sources, had high refusal rates due to religious reasons, while acceptance for autogenous bone grafting was high. 26,27,28 There is paucity of published literature regarding the constituents of animalbased products used in dentistry. The dental industry has witnessed a rapid growth in the last two decades, especially in the field of implantology and a wide range of new materials and products are being introduced in dentistry.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies involving participants who are Muslim found bone graft materials based on xenografts, especially from porcine sources, had high refusal rates due to religious reasons, while acceptance for autogenous bone grafting was high. 26,27,28 There is paucity of published literature regarding the constituents of animalbased products used in dentistry. The dental industry has witnessed a rapid growth in the last two decades, especially in the field of implantology and a wide range of new materials and products are being introduced in dentistry.…”
Section: Discussionmentioning
confidence: 99%
“…They reported that EMD could enhance bone regeneration through Akt/VEGF signaling in diabetic rats . Despite its bone regeneration potential, EMD has some difficulties such as animal sources, immunogenicity, regulatory assessments, ethical issues, large molecular weight (100–200 amino acids), and instability in vivo . , In this study, we compared the osteoimmunomodulatory potential of EMD with strontium ions under the same in vivo conditions to investigate whether it is worth to coat a layer of EMD with the mentioned difficulties for inducing bone regeneration or we can consider using other alternatives such as ions as a simpler and cheaper surface modification strategy.…”
Section: Introductionmentioning
confidence: 99%